The Relationship Between Gadget Usage Patterns and The Incidence of Asthenopia Among Junior High School Students in Mataram - Savitri, Komang Dewi; Geriputri, Ni Nyoman; Andari, Marie Yuni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Gadget use among junior high school students continues to rise, clearly contributing to asthenopia through extended exposure and inadequate self-regulation. This study directly assesses the impact of gadget use on asthenopia among junior high school students in Mataram City. Observational analytical research using a cross-sectional design enrolled 118 participants via simple random sampling. Data collected from gadget-use questionnaires and the Visual Fatigue Index (VFI) were analyzed with chi-square tests and binary logistic regression. Results confirmed that 57.6% of participants demonstrated poor usage habits, while 31.4% experienced asthenopia. No statistically significant relationship was found between overall gadget use and asthenopia (p = 0.785). Nonetheless, device use exceeding 2 hours emerged as the primary factor linked with asthenopia. In summary, poor gadget use is widespread, and prolonged use increases the risk of asthenopia, although this study did not find a significant overall link. Eye itching clearly dominated reported symptoms. To advance understanding and support student well-being, future research must employ objective measures of visual function and develop effective strategies for healthier use of devices.